Declining Dynamism and Countercyclical Labor Productivity - Olivares, Edward. (2017)
Abstract: Over the past several decades, average U.S. labor productivity has become more countercyclical. That is, it is more likely to increase during recessions. Over a similar time period, the pace of firm and labor market turnover has fallen. I document a relationship between these trends using state level data and in a model of on-the-job search, examine potential labor market changes that can account for both declining dynamism and increasingly countercyclical productivity. I find that a relative decline in matching efficiency at high-productivity firms can account for these facts, and review evidence that such a matching efficiency wedge has developed.; Thesis (M.S.)--Tufts University, 2017.; Submitted to the Dept. of Economics.; Advisor: Alan Finkelstein-Shapiro.; Keyword: Economics.